2003
DOI: 10.1080/1355260031000149154
|View full text |Cite
|
Sign up to set email alerts
|

Children and young people accused of child sexual abuse: A study within a community

Abstract: This paper reports on a study of 227 children and young people, all living in a West Midlands city in the UK, who between November 1993 and December 1999 were accused of having sexually abused a child. The study had two main objectives: first to examine the alleged behaviours, family backgrounds and personal characteristics of the young people; and second to discover what factors, if any, may be associated with recidivism later in adulthood. It is still too early to draw firm conclusions regarding recidivism, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 25 publications
3
24
0
Order By: Relevance
“…This is consistent with other studies who have reported high reoffense rates for nonsexual crimes (Elliot, 1994;Kahn & Chambers, 1991;Sipe, Jensen, & Everett, 1998;Taylor, 2003; Weinrott, 1996). The overall reconviction rate for the sample of sexual offenders was lower than that of the violent offender sample.…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with other studies who have reported high reoffense rates for nonsexual crimes (Elliot, 1994;Kahn & Chambers, 1991;Sipe, Jensen, & Everett, 1998;Taylor, 2003; Weinrott, 1996). The overall reconviction rate for the sample of sexual offenders was lower than that of the violent offender sample.…”
Section: Discussionsupporting
confidence: 92%
“…Of the young people responding, 13 were male and one was female. This reflects the overwhelmingly male nature of adolescent sexual aggression, which is noted in many other studies (for example, Taylor, 2003). In contrast, eight of the nine completed questionnaires from parents were from women, and in the ninth case a mother and father had filled in the questionnaire together.…”
Section: Resultsmentioning
confidence: 86%
“…It must be borne in mind that such terminology implies that children are similar to adult sex offenders and engage in sexual activities for gratification of their own sexual needs. Most young children who display SIB do not follow these patterns (Dey & Print, 1998), do not normally engage in such behaviours for own sexual gratification (Cavanagh-Johnson & Doonan, 2005) or grow up to become juvenile or adult sex offenders (Carpentier, Silovsky & Chaffin, 2006;Taylor, 2003). By using terminology derived from adults, the potential threat such children pose to society may be overemphasized, increasing demands for protection from such children.…”
Section: Discussionmentioning
confidence: 96%